Kesiapan perpustakaan SMA Muhammdiyah 2 Bandar Lampung dalam pengembangan website E-Perpustakaan - Arnila Purnamayanti; Nanda Oktaria (Faculty of Communication, Padjadjaran University, 2022)
Information technology in libraries is applied to meet the needs of users in obtaining various information quickly, precisely, and accurately. A website-based library is one form of information technology support to optimize the use of library information and materials, as well as optimize the substantive work of librarianship, starting from the procurement, processing, circulation of library materials, retrieval and information dissemination. So that in its implementation, a readiness from various aspects is needed so that the system can run optimally in meeting user needs. The objectives to be achieved in this research are to find out the readiness of the Muhammadiyah 2 Senior High School library Bandar Lampung in developing the E-Library website, as well as to find out what inhibiting factors are in developing the E-Library website. The writing method uses qualitative-descriptive data and data collection techniques are carried out through observation, interviews, documentation, and literature review which are then processed by data analysis techniques. The results of this paper indicate that the readiness of the Muhammadiyah 2 Senior High School library Bandar Lampung in developing the E-Library website has not been fully maximized, to be able to develop a library automation system there are still obstacles such as the librarians who are there not yet fully able to develop and operate the website E-Libraries, there is still an inadequate internet network access, and the menu features on the E-Library website are still incomplete. So there is still a need for improvement in preparing the automation system in the library of Muhammadiyah 2 Senior High School Bandar Lampung, such as improving the menu feature system, internet network, and human resources so that the development process is more optimal.